Steps on the adhisthana with a chandrashila (moonstone) - Temples of India Project Team (Jio Institute, 2024)
Broken debris from the original temple assembled on the southeast face of the adhisthana. U-shaped rounded stones are assembled on the parapet (their position or purpose in the original temple is unknown). Steps lead up three levels to the main temple at the top. The steps on the adhisthana have a chandrashila (moonstone) on the third step. The moonstone is a hemispherical stone in the shape of the moon, placed at the entrance of Hindu temples and is designed to resemble a lotus flower.